Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar PAI - Yunie Nanditha; Wirdati Wirdati; Oktari Kanus (Prodi Pendidikan Keagamaan Islam, 2023)
Islamic Religious Education plays an important role in building a generation of noble human beings. However, in reality, learning outcomes in PAI subjects are still low. Based on the initial observations that the researchers made, it was found that the results of studying PAI in class IVD at SD Negeri 6 Kampung Lapai were still low. One reason is the use of learning models that are not yet good and not varied. One solution is to use the right and good learning model. The Number Head Together (NHT) model is a model that can be used by teachers in the learning process at school. The aim of the study was to see the effect of the Numbered Head Together (NHT) Cooperative Learning Model on learning outcomes in PAI subjects in Class IV SD Negeri 6 Kampung Lapai. The population in this study was class IV, which consisted of 103 students. The samples of this research are class IV B and class IVD. The sampling technique in this study used purposive sampling. Methods of data collection in this study using questionnaires and tests of student learning outcomes. Data analysis techniques in this study used descriptive statistical analysis and inferential analysis. Inferential analysis includes normality test, homogeneity test and hypothesis testing. The results of hypothesis testing show that Tcount = 9.396 > T-table = 4.806, so it can be stated that there is a significant influence between the Numbered Head Together (NHT) Cooperative Learning Model on student learning outcomes in PAI subjects.